PREVALENCE OF F. gigantica AND PATHOLOGICAL CHANGES IN LIVER OF SIMEULUE BUFFALO - Ikwan Jamil; Teuku Reza Ferasyi; Muhammad Hambal; Yudha Fahrimal; Razali Razali (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
The aim of this study was to identify the prevalence of fasciolosis of Simeulue’s buffalo using macroscopic approach by observing pathological changes in the liver. The sample were obtained from slaughterhouse in Sinabang. A number of 60 livers were obtained on July to September 2015 based on post mortem examination. From this sample, a total of 57 livers were found positive indication of infested by F. gigantica (95%). The length and width of F. gigantica was 25 mm and 7 mm. The body was flat as a leaf, blunt on posterior, gray, brown, transparant and do not have a real shoulder shapes. The liver which were not  infested with F. gigantica showed sharp edges and a very high degree of elasticity. On the other hand, in the infested liver was found F. gigantica in the bile duct and showed a color of pale, the dark brown exudate as well as objects looks like gravel. The buffaloes sample were supplied to the abattoir from the paddy fields or oil palm plantations area. In comparison, the buffaloes raised in both areas were not different on the pathological changes of liver. In conclusion, this study showed that simeulue’s buffalo is very prevalence to F. gigantica.